Macroeconomic and Global Composite Indexes that Affect JCI Performance - Ichsani, Sakina (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to determine the effect of macroeconomic and global composite indexes on the performance of the Indonesia Stock Index (JCI) for the period 2018-2019 using a monthly observation period. The research method used is verification analysis. In this study, the dependent variable is the JCI performance, while the independent variable consists of macroeconomic elements, such as inflation, exchange rates, Bank Indonesia (BI) interest rates, and the money supply (M2), and also a global composite index consisting of the Dow Jones index and the Shanghai Composite Index (SSEC). Data used is secondary data, published by Bank Indonesia, and financial reports that are reported to the Indonesia Stock Exchange. The population in this study is macroeconomic conditions in Indonesia and in the global composite period in January 2018-September 2019 that consists of 147 data points. The results showed that simultaneously inflation, exchange rate, BI rate, M2, Dow Jones Index, and SSEC had a significant effect on JCI with as much influence (72.63%). The results of this study also showed that partially exchange rates, M2 and SSEC, affect JCI, while inflation, the BI rate, and Dow Jones have no effect on JCI. Suggestions for this research are that the government and investors always pay attention to macroeconomic conditions in Indonesia and always monitor economic conditions in the world. Suggestions for other researchers are to increase the time period of the study and to add other macroeconomic variables and a global composite index.